Evaluation of the Incidence and the State of Prophylaxis of Deep Vein Thrombosis and Pulmonary Embolism in Orthopaedic Patients in Al-Husain Teaching Hospital in Nasiriya - Wahby Ghalib Shaty (University of Thi-Qar Journal of Science, 2019)
Thromboembolic disease affecting the venous circulation of the lower limbs and the pulmonary system is considered as a major source for morbidity and mortality in orthopaedic patients, both those who are trauma victims and those who underwent surgery. It includes two entities, deep venous thrombosis (DVT) and pulmonary embolism (PE). Clinical sequels of these include limb venous and arterial impairment as well as pulmonary vascular affection which can culminate in cardiogenic shock, which is a potentially lethal event. Over decades, there was intensive researching for the ideal methods for protection against these complications. The result was a lot of mechanical and pharmacological means which issued with both merits and demerits. In this study, we tried to evaluate several indices in regard to this topic in our locality. On the top of these is the state of awareness to the significance of these complications among those responsible for patient care provision. Also, to evaluate the various methods used regarding their frequency of usage and their effectiveness and the extent of employment of the low molecular weight heparins as considered now as the gold standard of prophylaxis. The final goal is to stress several recommendations that are aimed to raise the state of awareness to and handling of this medical problem.